Turismo intervención publica en Canarias: transición del modelo cuantitivo al cuaitativo - Ramón Diaz Hernandez (Études Caribéennes)
Faced with excesses tourism, the local government of the Canary Islands issued a judgement (4 / 2001), which reformulates General Guidelines of Territory and Tourism. The aim is to set up the basis of a model of sustainable island development, with emphasis on natural resource management in general and tourism in particular. This decision was accompanied by standards whose objective is to limit the construction of new buildings for hotels. Shortly thereafter, the Government issued the ruling 126/2001 which limited the development of tourism. Parliament adopted another decree, "Ley de Medidas Urgent en Materia de Ordenación del Territorio y del Turismo de Canarias" (July 2001) which determines the conditions required for hotels higher category. The Parliament also gives its agreement to stop 19/2003, "Directrices de Ordenación General y Directrices de Ordenación del Turismo de Canarias."